Studi Pendahuluan sebagai Dasar Pengembangan Media Booklet berbasis Discovery Learning - Qiara Nur Halifa; Nurul Fauziah (Lembaga Pengembangan Kinerja Dosen, 2025)
Preliminary study as the basis for development of discovery learning-based booklet media. The purpose of this study is to describe the data of the initial research stage obtained as a basis for developing learning media and learning based on research results that will be made in the future. The development model applied in this study is the Plomp model, which has reached the initial data investigation stage. Instruments for collecting data include interviews, observations, and questionnaires. The results of the student needs questionnaire revealed that students agreed that it was necessary to develop a discovery learning-based booklet with a percentage of 81.8%. The learning media that has been used in learning is less effective so that students are less able to understand the subject matter. So it can be concluded that there is a need for the development of booket media based on discovery learning of calm digestive system material in humans in grade VIII of SMPN Siak Hulu.